PsycEXTRA Dataset 2005
DOI: 10.1037/e538922013-207
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism in adolescent school students: Relations to motivation, achievement, and well-being

Abstract: Positive conceptions of perfectionism (Stoeber & Otto, 2006) suggest that striving for perfection is associated with positive characteristics and adaptive outcomes. To investigate whether this also holds for adolescent school students, a sample of 121 ninth-graders completed measures of perfectionism at school (striving for perfection, negative reactions to imperfection), perceived parental pressure to be perfect, motivation, school achievement, and well-being. Results showed that negative reactions to imperfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
(30 reference statements)
1
16
0
1
Order By: Relevance
“…Because we investigated performance with a training task, we measured striving for perfection and negative reactions to imperfection during training (Stoeber et al, in press). In line with findings from outside sports showing that striving for perfection is Perfectionism and Performance 8 associated with higher grades in students (Bieling et al, 2003;Stoeber & Rambow, 2007) and predicts better results in aptitude tests (Stoeber & Kersting, 2007), we expected striving for perfection during training to predict higher training performance and greater performance increments over the series of trials. In comparison, because the dimension of self-critical perfectionism has not shown any systematic association with performance (Stoeber & Otto, 2006), we had no specific expectations for negative reactions to imperfection and thus approached the relationships with this aspect of perfectionism in an exploratory fashion.…”
Section: Perfectionism and Performancesupporting
confidence: 60%
“…Because we investigated performance with a training task, we measured striving for perfection and negative reactions to imperfection during training (Stoeber et al, in press). In line with findings from outside sports showing that striving for perfection is Perfectionism and Performance 8 associated with higher grades in students (Bieling et al, 2003;Stoeber & Rambow, 2007) and predicts better results in aptitude tests (Stoeber & Kersting, 2007), we expected striving for perfection during training to predict higher training performance and greater performance increments over the series of trials. In comparison, because the dimension of self-critical perfectionism has not shown any systematic association with performance (Stoeber & Otto, 2006), we had no specific expectations for negative reactions to imperfection and thus approached the relationships with this aspect of perfectionism in an exploratory fashion.…”
Section: Perfectionism and Performancesupporting
confidence: 60%
“…Regarding the studies on perfectionism and academic performance, the overwhelming majority shows that perfectionistic strivings are positively associated with academic performance: students with higher levels of perfectionistic strivings show higher exam performance, higher individual grades, and a higher GPA than students with lower levels of perfectionistic strivings (Accordino, Accordino, & Slaney, 2000;Bieling, Israeli, Smith, & Antony, 2003;Blankstein, Dunkley, & Wilson, 2008;Blankstein & Winkworth, 2004;Brown et al, 1999;Castro & Rice, 2003;Enns, Cox, Sareen, & Freeman, 2001;Grzegorek, Slaney, Franze, & Rice, 2004;Kawamura, Frost, & Harmatz, 2002;Leenaars & Lester, 2006;Nounopoulos, Ashby, & Gilman, 2006;Rice & Ashby, 2007;Sevlever & Rice, 2010;Stoeber & Eismann, 2007;Stoeber & Rambow, 2007;Vandiver & Worrell, 2002;Verner-Filion & Gaudreau, 2010;Witcher, Alexander, Onwuegbuzie, Collins, & Witcher, 2007). In contrast, the relationship of perfectionistic concerns with academic performance is less clear.…”
Section: Academic Performance [H2]mentioning
confidence: 99%
“…Perfectionistic strivings have shown positive relations with hope of success, performance-approach and mastery goal orientations, and intrinsic motivation whereas perfectionistic concerns have shown positive relations with fear of failure, performance-approach and performance-avoidance goal orientations, and extrinsic motivation (e.g., Damian, Stoeber, Negru, & B ban, 2014;Stoeber & Eismann, 2007;Stoeber & Rambow, 2007). In addition, research with school students has shown that perfectionism is related to numerous characteristics PERFECTIONISM AND SCHOOL ENGAGEMENT 4 and processes that are closely linked to school engagement (e.g., effort invested in schoolwork, adaptive study strategies) and predictive of educational success (e.g., academic efficacy, academic achievement; Rice & Slaney, 2002; see also Stoeber, Edbrooke-Childs, & Damian, in press).…”
Section: Perfectionism and School Engagementmentioning
confidence: 99%